Fatal Necrotizing Fasciitis in a Child following a Blunt Chest Trauma - Yohel Ocaña; Rolando Ulloa-Gutierrez; Adriana Yock-Corrales (Case Reports in Pediatrics)
Necrotizing fasciitis is a serious soft tissue infection rarely occurring in children after blunt trauma. Due to its high morbidity and mortality rates, a high index of suspicion is necessary for prompt diagnosis and treatment. We describe a 6-year-old Costa Rican girl who died secondary to multiple complications following a posttraumatic necrotizing fasciitis.